A Case of Giant Dermoid Cyst at Sacrococcygeal in Adult at “X” Hospital in Bandung - Farid Yudoyono; Christian Ade; Dilli MA Pratama; Hasan Baraqbah; Adhitya R Yudhadi (Universitas Kristen Maranatha, 2023)
Dermoid cysts are benign tumors that can be found anywhere in the body. There is no dermoid cysts clear data yet in Indonesia. In the spine, these tumors generally occur in the lumbar region and are often accompanied by congenital spinal dysrafism and/or dermal sinus passages. Dermoid cysts arise from abnormal growth of the ectodermal folds during pregnancy. Its incidence is 0.7 – 1.8% of all central nervous system tumors. The aim of reported this case is to highlight the role of a diagnostic and evaluate the surgical outcome. A 47 year old female patient with a lump in the sacrococcygeal area measuring 20 x 18 x 16 cm, with hard and soft consistency. MRI images show a hypo and hyperintense mass without spinal deformity. After the tumor was removed, the patient was allowed to go home for the 2nd day without complications. In conclusion, extraspinal dermoid cyst is a rare case that requires special diagnostic and surgical modalities to provide better clinical results.